Polypharmacy to Mitigate Acute and Delayed Radiation Syndromes - Gasperetti, Tracy; Miller, Tessa; Gao, Feng; Narayanan, Jayashree; Jacobs, Elizabeth R.; Szabo, Aniko; Cox, George N.; Orschell, Christie M.; Fish, Brian L.; Medhora, Meetha (Frontiers in Pharmacology, 2021)
There is a need for countermeasures to mitigate lethal acute radiation syndrome (ARS) and delayed effects of acute radiation exposure (DEARE). In WAG/RijCmcr rats, ARS occurs by 30 days following total body irradiation (TBI), which manifests as potentially lethal gastrointestinal (GI) and hematopoietic toxicities after >12.5 and >7 Gy, respectively. DEARE, which includes potentially lethal lung and kidney injuries, are observed after partial body irradiation with one hind limb shielded (13 Gy, leg-out PBI). The goal of this study was to enhance survival from ARS and DEARE by polypharmacy, since no monotherapy has demonstrated efficacy to mitigate these multiple sequelae. For mitigation of ARS following 7.5 Gy TBI, a combination of three growth factors (polyethylene glycol (PEG) derivatives of granulocyte colony-stimulating factor (hG-CSF), granulocyte-macrophage colony-stimulating factor (mGM-CSF) and the cytokine Interleukin (hIL)-11) were tested. This triple combination (TC) enhanced survival by 30-days from ~25% to >60%. In previous studies, enrofloxacin, saline and the angiotensin converting enzyme inhibitor lisinopril, improved survival from GI-ARS and DEARE up to 160 days after 13 Gy leg-out PBI. In the current study, the TC given with lisinopril after 7.5 Gy TBI or 13 Gy leg-out PBI mitigated GI- and hematopoietic-ARS as well as DEARE. Secondary endpoints measuring circulating blood cell recovery as well as lung and kidney function after radiation were also improved by the TC + lisinopril. The combination enhanced survival as compared to PEG-hG-CSF (BBT-015) alone at 120-days following 13 Gy leg-out PBI. Taken together the results demonstrated compatible polypharmacy to mitigate radiation-induced ARS and DEARE in rats.